Hybrid Craft from a Postmodern Perspective: A Literature Review on the Deconstruction of the Fine Art–Craft Dichotomy in Contemporary Art Practices - Era Ramadhani (Ethnography : Journal of Cultural Anthropology, 2026)
The hierarchical separation of fine art and craft established by modernist discourse has increasingly been challenged in contemporary art. This study examines how postmodern thought supports the emergence of hybrid craft and how such practices deconstruct the fine art–craft dichotomy. Using a qualitative narrative literature review, the study analyzes scholarly books and journal articles addressing postmodern aesthetics, contemporary craft, hybridity, materiality, and interdisciplinary artistic practices. Sources were selected according to their conceptual relevance to the research focus and synthesized through thematic coding. The analysis identifies three interrelated characteristics of hybrid craft: media interdisciplinarity, technical hybridization, and conceptual experimentation. These characteristics are manifested in the combination of traditional craft techniques with installation, digital media, contemporary conceptual approaches, and new production technologies. The findings indicate that hybrid craft not only expands artistic materials and techniques but also repositions material knowledge, manual skill, creative process, and concept within the same field of contemporary artistic practice. This study offers a postmodern interpretive framework for understanding hybrid craft as a critical practice that destabilizes fixed disciplinary categories and renegotiates the relationship between fine art and craft